Pemahaman Penyelesaian Sengketa Tanah Melalui Mekanisme Non Litigasi Dan Litigasi Kepada Masyarakat Di Kelurahan Penggaron Lor Kota Semarang - Suwandi, Dedy; Triasih, Dharu; Setyowati, Endang (Fakultas Hukum Universitas Semarang, 2025)
The resolution of land disputes through non-litigation and litigation mechanisms is a common issue faced by the community, especially concerning inheritance and land boundary problems that involve families and local environments. In Penggaron Lor Village, Genuk District, Semarang City, many residents lack a deep understanding of these two mechanisms, despite their importance in choosing the appropriate dispute resolution path based on the context and needs of the parties involved. To address this, the Faculty of Law of Semarang University carried out a community service program to educate the public about both litigation and non-litigation land dispute resolution mechanisms. The method used in this program is a normative-prescriptive approach, utilizing legal, historical, and conceptual perspectives. The community service activities consisted of a pre-test to assess initial knowledge, a lecture on litigation and non-litigation mechanisms, and a question-and-answer session to deepen participants' understanding. The results of the program indicate that most people in Penggaron Lor Village are not fully aware of how to resolve land disputes through either litigation (court) or non-litigation (such as mediation and conciliation) methods. However, the majority of participants prefer non-litigation resolution methods as they are considered more efficient and help maintain good relationships between the parties involved in the dispute. Additionally, some community representatives are expected to become follow-up counselors, spreading this knowledge to a wider audience. Keywords: Land Dispute; Litigation; Non-Litigation.